Targeting lipid metabolism of macrophages: A new strategy for tumor therapy - Nan Shao; Hui Qiu; Jing Liu; Daimin Xiao; Juanjuan Zhao; Chao Chen; Jiajia Wan; Mengmeng Guo; Guiyou Liang; Xu Zhao; Lin Xu (Journal of Advanced Research)
Background: Lipid metabolism has been implicated in a variety of normal cellular processes and strongly related to the development of multiple diseases, including tumor. Tumor-associated macrophage (TAM) has emerged as a crucial regulator in tumorigenesis and promising target for tumor treatment.Aim of review: A thorough understanding of TAM lipid metabolism and its value in tumorigenesis may provide new ideas for TAM-based anti-tumor therapy.Key scientific concepts of review: TAMs can be divided into two main types, M1-like TAMs and M2-like TAMs, which play anti-tumor and pro-tumor functions in tumor occurrence and development, respectively. Accumulating evidence has shown that lipid metabolic reprogramming, including fatty acid uptake and utilization, cholesterol expulsion, controls the polarization of TAMs and affects the tumorgenesis. These advances in uncovering the intricacies of lipid metabolism and TAMs have yielded new insights on tumor development and treatment. In this review, we aim to provide an update on the current understanding of the lipid metabolic reprogramming made by TAMs to adapt to the harsh tumor microenvironment (TME). In particular, we emphasize that there is complex lipid metabolism connections between TAMs and distinct tumors, which influences TAM to bias from M1 to M2 phenotype in tumor progression, and ultimately promotes tumor occurrence and development. Finally, we discuss the existing issues on therapeutic strategies by reprogramming TAMs based on lipid metabolism regulation (or increasing the ratio of M1/M2-like TAMs) that could be applied in the future to clinical tumor treatment.